2021
DOI: 10.1111/jace.17786
|View full text |Cite
|
Sign up to set email alerts
|

Flash sintering produces eutectic microstructures in Al2O3–LaPO4 versus conventional microstructures in 8YSZ–LaPO4

Abstract: Flash sintering is a novel manufacturing technique that applies an electrical field across a ceramic green body, while heating it in a furnace. [1][2][3] As the material sinters, the current induces joule heating, which assists in fast densification or enhanced reaction mixing. Over the past decade, flash sintering has shown promise in reducing sintering costs, increasing densification efficiency, promoting reaction sintering, etc. 4 In the current era of energy conservation to preserve the environment, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…As an example, Figure shows reactive flash sintered Al 2 O 3 –LaPO 4 composites which display eutectic microstructures in the current‐localized region. [ 88 ] This work also demonstrated that Al 2 O 3 –LaPO 4 is a eutectic forming system, however, mechanical properties were not reported.…”
Section: Reactive (Reaction) Flash Sinteringmentioning
confidence: 77%
See 3 more Smart Citations
“…As an example, Figure shows reactive flash sintered Al 2 O 3 –LaPO 4 composites which display eutectic microstructures in the current‐localized region. [ 88 ] This work also demonstrated that Al 2 O 3 –LaPO 4 is a eutectic forming system, however, mechanical properties were not reported.…”
Section: Reactive (Reaction) Flash Sinteringmentioning
confidence: 77%
“…The first eutectic composition processed via RFS was Al 2 O 3 –Y 2 O 3 to achieve Al 2 O 3 –Y 3 Al 5 O 12 (YAG) ceramics, but eutectic microstructures were not reported. [ 83 ] Later, eutectic microstructures were found in this same Al 2 O 3 –YAG system, [ 84,85 ] and also in Al 2 O 3 –ZrO 2 , [ 86 ] Al 2 O 3 –GdAlO 3 –ZrO 2 , [ 87 ] LaPO 4 –Al 2 O 3 , [ 88 ] and 3YSZ–Al 2 O 3 . [ 89 ] In the case of Al 2 O 3 –YAG, Liu et al [ 84 ] reported that the RFSed specimens exhibited better mechanical properties (e.g., hardness of 18.5 ± 0.3 GPa, and toughness of 4.3 ± 0.2 MPa m 1/2 ) than materials made by traditional directional solidification.…”
Section: Reactive (Reaction) Flash Sinteringmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, with the flash event, the eutectic reaction would proceed even at a furnace temperature lower than the eutectic temperature because of the increase in specimen temperature. For example, Al 2 O 3 –LaPO 4 , Al 2 O 3 –GAP–ZrO 2 , and Al 2 O 3 –Y 3 Al 5 O 12 ceramics with eutectic microstructure were consolidated from raw powder mixtures at eutectic compositions using flash sintering 10–12 …”
Section: Introductionmentioning
confidence: 99%